DAMPAK KELUARGA BROKEN HOME DALAM MOTIVASI BELAJAR KELAS VII SMP 24 PONTIANAK - Nadia Agustianingsih; Indri Astuti; Yuline Yuline (Universitas Tanjungpura, 2019)
AbstractThe impact of broken home parents’ conditions on students’ learning motivation is the reality that has a negative implication for health personality expansion, and environment factor in personality expansion. However, broken home factor has a big role nowadays. This research used descriptive method and the research form was survey research form. The subject of this research was five students, one guidance teacher, and five students’ friends. This research used qualitative approach. Data collection techniques were observation, interview, and documentation. Based on the result of this research, the impact of broken home parents in students’ learning motivation on grade seventh of SMP Negeri 24 Pontianak influences students’ learning outcomes and also the behavior of students. Impact was divided into two, namely positive and negative. One student had very good learning motivation and four students were experience low learning motivation. Student learning outcomes as well as students influenced in grade VII of SMP Negeri 24 Pontianak are influenced by the broken impact of student learning motivation.Keywords: Broken Home Family, Impact, Learning Motivation